An Empirical View of Business Ethics on Private College in Kuantan: A Case Study - Diyana, Kamarudin; Haziman, Zakaria; Wan Khairul Anuar, Wan Abd Manan (KnE Social Sciences, 2019)
Private institutions in Malaysia are bound to the Private Higher Institution Act 1996, normally relies on corporate investment to sustain their operations. Data from Department of statistic Malaysia show that there is a significant incensement of gross output value in the education sector in Malaysia from RM 17.6 billion in 2017 compared to RM 15.2 billion in 2015 which reflect the business competencies in private institution (Ministry of Education Malaysia, 2015). In this research, a case study will be conducted at one of the private colleges in Kuantan, Pahang. The aim of this research is to analyze the ethical issue regarding business ethics using a semi-structured interview method with college staff and students. The interviews were recorded and transcribed. Each case would be analyzed, discussed and the cases would be related to the business ethics concept and ethical principle. This study aims to create good moral value and business ethics that can be practiced in the private education sector in Malaysia.